Heuristic performance on inventory routing with logistic ratio - Kwabena Ntim, Amponsah (2016)
The inventory routing problem (IRP) is a hard combinatorial optimization problem, where a supplier is responsible for maintaining the inventory levels of customers to keep them from running out of product, while maintaining low overall delivery costs. The IRP involves routing and scheduling decisions, and the search space grows exponentially with problem size. Although most of the IRP literature focuses on the objective of minimizing delivery costs over a planning horizon, the logistic ratio (delivery cost per unit of product) has been identified in some studies on real-life companies as a potentially better measure of cost efficiency. This study compares the long term cost difference between optimizing cost and optimizing the logistic ratio by running a series of computational experiments. From the results, it emerges that although optimizing the logistic ratio is indeed beneficial in many cases, optimizing cost may be better in the long term for some problem instances, particularly those with short planning horizons